2023
DOI: 10.29244/jfs.v8i1.45096
|View full text |Cite
|
Sign up to set email alerts
|

Economic Pressure and Debt Decision-Making of the Customer's Family Bank Keliling/Bank Emok

Ranti Rosanti,
Euis Sunarti

Abstract: Difficult economic conditions often force families to borrow money from bank keliling/bank emok. This study analyzes the effect of family characteristics, debt characteristics, economic pressure before debt, and debt decision-making on economic pressure after debt. In particular, this study distinguishes economic pressures before and after debt. The research design used is a retrospective and cross-sectional study involving 60 wives of customers of bank keliling/bank emok selected by simple random sampling. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
1
1
Order By: Relevance
“…This indirectly made the debt interest larger than the stipulated interest rate (>25%). This is relatively higher than the research by Rosanti and Sunarti (2023), who found that Bank Emok customers were charged 20 percent to 25 percent interest. Bank Emok offers debt limits starting from IDR 2,000,000 and gives customers the right to top up, i.e., increase the debt amount when they have paid half (50%) of the previous installment.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…This indirectly made the debt interest larger than the stipulated interest rate (>25%). This is relatively higher than the research by Rosanti and Sunarti (2023), who found that Bank Emok customers were charged 20 percent to 25 percent interest. Bank Emok offers debt limits starting from IDR 2,000,000 and gives customers the right to top up, i.e., increase the debt amount when they have paid half (50%) of the previous installment.…”
Section: Discussioncontrasting
confidence: 55%
“…Families with debts worth more than half the value of their assets show high economic pressure (Firdaus & Sunarti, 2009). Rosanti and Sunarti (2023) found that family economic pressure increased after borrowing from Bank Emok. Previous research has found that family welfare is affected by economic pressure (Laily & Sunarti, 2022;Sunarti, 2018;Sunarti et al, 2021).…”
Section: Introductionmentioning
confidence: 99%